2011
DOI: 10.1111/j.1365-2125.2010.03839.x
|View full text |Cite
|
Sign up to set email alerts
|

Improving the quality of drug research or simply increasing its cost? An evidence‐based study of the cost for data monitoring in clinical trials

Abstract: WHAT IS ALREADY KNOWN ABOUT THIS SUBJECT• Current knowledge is based on practical experience. This paper presents the first novel, quantitative and qualitative view on the efficacy of the sponsor query system widely applied in the pharmaceutical industry, used for quality control purposes by data management for clinical data. WHAT THIS STUDY ADDS• This study presents a structured view on the process of clinical data management and sponsor queries, the efficacy and cost effectiveness of sponsor queries and dual… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
17
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(19 citation statements)
references
References 6 publications
2
17
0
Order By: Relevance
“…Another interesting point was the cost analysis, which confirmed that the cost of data quality assurance is linked to both monitoring and DM, and that lowering monitoring requirements increases the DM workload. We showed that, provided our assumption of the cost of a query is reliable, the differential cost per patient could reach more than 100 euros, which is consistent with Pronker's assumptions in an evidence-based study on clinical data-management cost [28]. Beyond the financial analysis, we need to consider the typology of the data corrected with SDV and with DM.…”
Section: Discussionsupporting
confidence: 73%
“…Another interesting point was the cost analysis, which confirmed that the cost of data quality assurance is linked to both monitoring and DM, and that lowering monitoring requirements increases the DM workload. We showed that, provided our assumption of the cost of a query is reliable, the differential cost per patient could reach more than 100 euros, which is consistent with Pronker's assumptions in an evidence-based study on clinical data-management cost [28]. Beyond the financial analysis, we need to consider the typology of the data corrected with SDV and with DM.…”
Section: Discussionsupporting
confidence: 73%
“…A related analysis was performed by Pronker and colleagues focusing on sponsor queries, defined as discrepancies identified in data entered in the eCRF while the trial was on going. The authors concluded that very few queries were sent regarding data points which were critical to the trial end points (0.001% of all data points), leaving a poor cost‐effectiveness ratio and the authors encouraged the development of a risk‐assessment oriented monitoring of clinical trial data .…”
Section: Discussionmentioning
confidence: 99%
“…One recent study examined the usefulness of 100% SDV in a cancer trial dataset from 75 sites in the United Kingdom [9]. The discrepancies found when comparing the data before and after the 100% SDV were mostly random errors which, because evenly distributed across arms, had no significant impact on the primary outcomes.. Another study reviewed sponsor queries from the datasets of three different Phase I studies conducted by one contract research organization in the Netherlands [10]. Only 0.4% (6/1389) of the query-driven data changes could have influenced the primary study results.…”
Section: Introductionmentioning
confidence: 99%